Genome sequence analysis of bos frontalis and genome wide association study (GWAS) between near species - Islam, Sara; Parvin, Rumana; Afrin, Most. Sanjida; Babu, Liakot Khan; Sarkar, Oindri Aurunima (BRAC University, 2021)
Cataloged from PDF version of thesis.